If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(2x-3)=2x-3
We simplify the equation to the form, which is simple to understand
(2x-3)=2x-3
Remove unnecessary parentheses
2x-3=2x-3
We move all terms containing x to the left and all other terms to the right.
+2x-2x=-3+3
We simplify left and right side of the equation.
0x=0
0=0
This equation is an identity, so all real numbers are solutions.
| 2tg|x-3.14/6| | | 3y=12+15 | | x=6/5*17 | | 2xsquared-4x-7=0 | | (x-2)=2x-3 | | 12/5z=11/8 | | Xlog(3/5)=1-xlog7 | | 2x(10+2x)=3x^2 | | (5+x)2-(3x-4)(5+x)=0 | | 2y+2=34 | | X-2((X+2)+(X-2))=x^2 | | X+6*5x+12= | | 2x-2-5x-10=3x-12 | | 3m^2=6m+5 | | (8x^6)^-1/3 | | x+1/4=7 | | (12x-5)/(5x-4) | | 6(x+5)=9(x+3) | | 5y-3=7-2y | | 9(x-6)=5(x-10) | | 31=0.41ln(x+1) | | 32u+4= | | 502000=16x-534000 | | ln(x)=ln(3)+ln(5)-ln(x) | | 6x+5y=156 | | x+49=5x+17 | | x+(x+15)=35 | | 9k+-3s= | | P(x)=3x+200 | | cos(2x)+cos(3x)-cos(4x)=0 | | 2(x+3)-5=4x-(x+3) | | 2y+12=7y+26 |